Circadian Clocks and Cancer: Timekeeping Governs Cellular Metabolism. (July 2019) - Verlande, Amandine; Masri, Selma
Abstract : The circadian clock is a biological mechanism that dictates an array of rhythmic physiological processes. Virtually all cells contain a functional clock whose disruption results in altered timekeeping and detrimental systemic effects, including cancer. Recent advances have connected genetic disruption of the clock with multiple transcriptional and signaling networks controlling tumor initiation and progression. An additional feature of this circadian control relies on cellular metabolism, both within the tumor microenvironment and the organism systemically. A discussion of major advances related to cancer metabolism and the circadian clock will be outlined, including new efforts related to metabolic flux of transformed cells, metabolic heterogeneity of tumors, and the implications of circadian control of these pathways. Highlights: The circadian clock is a biological pacemaker mechanism that precisely controls rhythms in behavior and physiological functions controlling endocrinology, metabolism, and immune response. Disruption of circadian rhythms has been reported to adversely alter normal physiology and results in disorders linked to metabolism, mood regulation, sleep behavior, and cancer. Clinical data has shown that mutations and changes in expression of core clock genes is reported in several human cancers. Use of genetic mouse models and cell lines have delineated the crosstalk of the circadian clock with several pathways linked to oncogenes and tumor suppressors, such as c-Myc, Ras, PTEN, and p53. The circadian clock governs metabolic pathways regulating glucose utilization, amino acid uptake, lipogenesis, and β-oxidation. Therefore, deregulation of circadian rhythms impinges on metabolism and subsequent proliferation of cancer cells, which can provide new avenues for therapeutic intervention.